2005
DOI: 10.1097/01.hjr.0000173110.21851.a9
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for prolonged QTc among US adults: Third National Health and Nutrition Examination Survey

Abstract: Healthcare practitioners should be aware that a prolonged QTc interval is a potential indicator of cardiovascular risk, and should exercise caution in prescribing potentially QT-prolonging medications to certain patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
103
2
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(114 citation statements)
references
References 44 publications
6
103
2
3
Order By: Relevance
“…We found a prolonged QTc interval in nearly 47% of our cohort IBD population, which was clearly higher, than that (8.7%) in the general population published in previous studies (3). A study utilizing the Third National Health and Nutrition Examination Survey demonstrated that the prevalence of QTc interval prolongation in individuals aged >40 years was 6.3% (21). Similarly in the Framingham study Goldberg et al (22), the prevalence of QTc interval prolongation between the age groups of 30 and 62 years was 5.4%.…”
Section: Discussioncontrasting
confidence: 43%
See 1 more Smart Citation
“…We found a prolonged QTc interval in nearly 47% of our cohort IBD population, which was clearly higher, than that (8.7%) in the general population published in previous studies (3). A study utilizing the Third National Health and Nutrition Examination Survey demonstrated that the prevalence of QTc interval prolongation in individuals aged >40 years was 6.3% (21). Similarly in the Framingham study Goldberg et al (22), the prevalence of QTc interval prolongation between the age groups of 30 and 62 years was 5.4%.…”
Section: Discussioncontrasting
confidence: 43%
“…The main risk factors implicated in QT interval prolongation appear to be hypocalcemia, hyperkalemia, hypomagnesaemia, diabetes, hypertension, female gender, higher BMI, cardiac disease, gene mutations, medications (antiarrhythmics, antibiotics, antipsychotics, and antidepressants) (21,24,25). In our study, except for higher BMI, which was significantly associated with prolonged QTc interval (26.2±5.9 vs. 29.7±6.9, p=0.005), other risk factors, such as female gender, hypertension, CAD, Table 4.…”
Section: Discussionmentioning
confidence: 99%
“…A higher prevalence of QTc prolongation in women than in men has been previously reported (8). We have also recently reported a higher prevalence of ECGdiagnosed left ventricular hypertrophy in women compared with men with type 1 (18) or type 2 (22) diabetes.…”
Section: Results -mentioning
confidence: 53%
“…The pathogenesis of QTc prolongation remains poorly understood, although cross-sectional studies suggest a role for several risk factors, including female sex (8), glycemic control (9), ischemic heart disease (10), gene mutations (11), and blood pressure (12). The identification of risk factors for prolonged QTc is of clinical relevance because it would enable the targeting of people at high risk of cardiovascular events and, potentially, the application of risklowering strategies.…”
mentioning
confidence: 99%
“…The standard 12-lead electrocardiogram (ECG), which provides information about the QT interval, is a representation of depolarization and repolarization of the ventricular myocytes. Thus, it is assumed that the increased QTd observed in cardiac diseases with heterogeneous ventricular recovery times reflects the disparity of ventricular recovery times (8,9). The QTd is a simple, inexpensive and noninvasive method to measure underlying dispersion recovery of ventricular excitability.…”
mentioning
confidence: 99%